Personal factors shaping pre-service math and science teachers' attitudes: An SEM study - Aisyah, Nyimas; Ismet, Ismet; Hiltrimartin, Cecil; Sriyanti, Ida; Silvhiany, Sary; Meilinda, Meilinda (LPMPP Universitas Negeri Yogyakarta, 2024)
Climate change demands urgent attention from both teachers and students. As pivotal agents of change, preservice teachers play a crucial role in shaping a generation that values and conserves the environment. This study investigated how academic background (mathematics/science vs. non-mathematics/science) influences preservice teachers' attitudes toward climate change and their value orientations. The study included 287 mathematics/science and 182 non-mathematics/science preservice teachers who completed a 50-item questionnaire. Structural Equation Modeling (SEM) was employed to analyze the gathered data. The findings indicated that academic background did not significantly influence preservice teachers' value orientations or attitudes toward climate change. This suggests the presence of other influential factors not examined in this study. Given these results, adopting a comprehensive, interdisciplinary approach to environmental education is imperative. Such an approach can better equip preservice teachers with the knowledge and skills needed to effectively engage students in understanding and addressing climate change. Further research should focus on identifying these additional influencing factors. This will enable educators to refine environmental education strategies, fostering a future generation that values and actively contributes to environmental stewardship.